Meta-Analysis of Corticosteroids in the Management of Sepsis: Evaluating Efficacy and Safety - Harvindra, Astrid; Armen Ahmad (HM Publisher, 2024)
Background: Sepsis remains a significant cause of morbidity and mortality worldwide. Corticosteroids have been used in sepsis management, but their efficacy and safety remain debated. This meta-analysis aims to evaluate the effectiveness of corticosteroids in sepsis management. Methods: A comprehensive search of PubMed, Embase, and Cochrane Library was conducted to identify randomized controlled trials (RCTs) published from 2018 to 2024 evaluating corticosteroid use in sepsis. The primary outcome was mortality. Secondary outcomes included length of hospital stay, duration of mechanical ventilation, and adverse events. Data were pooled using a random-effects model, and heterogeneity was assessed using the I² statistic. Results: Twenty-one RCTs (n=12,350 patients) were included. Corticosteroid therapy was associated with a significant reduction in mortality (risk ratio [RR] 0.87, 95% confidence interval [CI] 0.79-0.96, p=0.004). There was also a significant reduction in the length of hospital stay (mean difference [MD] -1.5 days, 95% CI -2.3 to -0.7, p<0.001) and duration of mechanical ventilation (MD -1.2 days, 95% CI -1.9 to -0.5, p<0.001). No significant increase in adverse events was observed. Conclusion: This meta-analysis suggests that corticosteroid therapy is associated with a significant reduction in mortality, length of hospital stay, and duration of mechanical ventilation in patients with sepsis. The benefits appear to outweigh the risks. Corticosteroids should be considered as part of the standard of care in sepsis management.